Performance of a Dual Human Immunodeficiency Virus/Syphilis Rapid Test Compared With Conventional Serological Testing for Syphilis and Human Immunodeficiency Virus in a Laboratory Setting: Results From the Zimbabwe STI Etiology Study. Issue 9 (September 2019) - Rietmeijer, Cornelis A.; Mungati, More; Kilmarx, Peter H.; Barr, Beth Tippett; Gonese, Elizabeth; Kularatne, Ranmini S.; Lewis, David A.; Klausner, Jeffrey D.; Rodgers, Luanne; Handsfield, H. Hunter
Abstract : Background: Dual human immunodeficiency virus (HIV)/syphilis rapid, point-of-care testing may enhance syphilis screening among high-risk populations, increase case finding, reduce time to treatment, and prevent complications. We assessed the laboratory-based performance of a rapid dual HIV/syphilis test using serum collected from patients enrolled in the Zimbabwe Sexually Transmitted Infections (STI) Etiology study. Methods: Blood specimens were collected from patients presenting with STI syndromes in 6, predominantly urban STI clinics in different regions of Zimbabwe. All specimens were tested at a central research laboratory using the Standard Diagnostics Bioline HIV/Syphilis Duo test. The treponemal syphilis component of the dual rapid test was compared with the Treponema pallidum hemagglutination assay (TPHA) as a gold standard comparator, both alone or in combination with a nontreponemal test, the rapid plasma reagin test. The HIV component of the dual test was compared with a combination of HIV rapid tests conducted at the research laboratory following the Zimbabwe national HIV testing algorithm. Results: Of 600 men and women enrolled in the study, 436 consented to serological syphilis and HIV testing and had specimens successfully tested by all assays. The treponemal component of the dual test had a sensitivity of 66.2% (95% confidence interval [CI], 55.2%–77.2%) and a specificity of 96.4% (95% CI, 94.5%–98.3%) when compared with TPHA; the sensitivity increased to 91.7% (95% CI, 82.6%–99.9%) when both TPHA and rapid plasma reagin were positive. The HIV component of the dual test had a sensitivity of 99.4% (95% CI, 98.4%–99.9%) and a specificity of 100% (95% CI, 99.9%–100%) when compared with the HIV testing algorithm. Conclusions: Laboratory performance of the SD Bioline HIV/Syphilis Duo test was high for the HIV component of the test. Sensitivity of the treponemal component was lower than reported from most laboratory-based evaluations in the literature. However, sensitivity of the test increased substantially among patients more likely to have active syphilis for which results of both standard treponemal and nontreponemal tests were positive. Abstract : The sensitivity of the treponemal component of the dual HIV/syphilis rapid test was 66.2% when compared with the comparator treponemal test. Sensitivity increased to 91.7% when comparator treponemal and nontreponemal tests were both positive. Sensitivity and specificity for the HIV component of the rapid test were 99.9% and 100%, respectively.